2010
DOI: 10.1038/npp.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Attenuates the Appetitive Effects of Δ9-Tetrahydrocannabinol in Humans Smoking Their Chosen Cannabis

Abstract: Worldwide cannabis dependence is increasing, as is the concentration of Delta(9)-tetrahydrocannabinol (THC) in street cannabis. At the same time, the concentration of the second most abundant cannabinoid in street cannabis, cannabidiol (CBD), is decreasing. These two cannabinoids have opposing effects both pharmacologically and behaviorally when administered in the laboratory. No research has yet examined how the ratio of these constituents impacts on the appetitive/reinforcing effects of cannabis in humans. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(164 citation statements)
references
References 33 publications
12
146
3
3
Order By: Relevance
“…Yet most studies show that neither smoked, vaporized nor oral CBD alters THC's positive subjective effects, such as feeling 'high' or 'stoned' (Juckel et al, 2007;Roser et al, 2009;Morgan et al, 2010;see Zhornitsy and Potvin, 2012;Hindocha et al, 2015). There are several explanations for this lack of consistency.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Yet most studies show that neither smoked, vaporized nor oral CBD alters THC's positive subjective effects, such as feeling 'high' or 'stoned' (Juckel et al, 2007;Roser et al, 2009;Morgan et al, 2010;see Zhornitsy and Potvin, 2012;Hindocha et al, 2015). There are several explanations for this lack of consistency.…”
Section: Introductionmentioning
confidence: 88%
“…For example, the subjective effects of nabiximols (oromucosal spray containing equal parts CBD and THC) did not differ from a comparable dose of oral THC alone (Schoedel et Oral cannabidiol and smoked cannabis M Haney et al did not alter ratings of 'stoned' following vaporized THC administration (Hindocha et al, 2015); and, cannabis smoked naturalistically (participant's own self-selected marijuana) with high CBD did not produce different ratings of 'stoned' than cannabis with low CBD concentrations (Morgan et al, 2010). Furthermore, there was no indication that cannabis bred to contain different levels of CBD (0.2, 1.0%) altered the subjective, physiological, or performance effects of smoked cannabis with varying THC concentrations (1.8, 3.6% THC; Ilan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The same investigative team has also evaluated CBD in relation to cannabis abuse. In naturalistic studies conducted with cannabis users, the concentration of CBD in smoked cannabis did not attenuate psychomimetic symptoms in participants when they were acutely intoxicated [80]; however, CBD reduced Bwanting^and Bliking^of cannabis-related stimuli [81]. Additionally, a case report in 1 patient indicated that CBD might reduce withdrawal symptoms and the amount of cannabis smoked upon resumption of cannabis use, but no systematic study has been conducted in relation to CBD and cannabis relapse behavior.…”
Section: Cbd and Human Translational Studiesmentioning
confidence: 97%
“…Epidemiological studies of various neuropsychiatric disorders indicate that a higher CBD content in chronically consumed cannabis may protect against adverse effects of THC, including psychotic symptoms, drug cravings, memory loss, and hippocampal gray matter loss [115][116][117][118] (reviewed in [119]). As THC acutely induces anxiety, this pattern may also be evident for chronic anxiety symptoms.…”
Section: Evidence From Epidemiological and Chronic Studiesmentioning
confidence: 99%